Bioelectrodynamics and biocommunication (World scientific, 1994)
This collection of papers covers the role of electrodynamical activities in biocommunication. The book features research findings, practical applications and theoretical investigations linking phenomena such as the sensitivity of organisms to ultraweak ELF electromagnetic fields.